The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3748/wjg.v28.i23.2546
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation in the metabolic diseases: Current status and perspectives

Abstract: With the development of microbiology and metabolomics, the relationship between the intestinal microbiome and intestinal diseases has been revealed. Fecal microbiota transplantation (FMT), as a new treatment method, can affect the course of many chronic diseases such as metabolic syndrome, malignant tumor, autoimmune disease and nervous system disease. Although the mechanism of action of FMT is now well understood, there is some controversy in metabolic diseases, so its clinical application may be limited. Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 138 publications
0
17
0
Order By: Relevance
“…In CD, CEACAM6 is a receptor for AIEC in the intestinal mucosa, and increased CEACAM6 expression on the apical membrane of ileum cells promoted the abnormal colonization of AIEC in the ileum mucosa[ 9 ]. Furthermore, AIEC LF82 type I pili binding to CEACAM6 and TLR5 induced hiF-1A production and activated the classic NF-κB pathway, resulting in clinical colitis symptoms[ 10 ]. To mimic the high level of CEACAM6 expression in CD, transgenic CEABAC10-expressing mice were used to establish models expressing human CEACAMs.…”
Section: Introductionmentioning
confidence: 99%
“…In CD, CEACAM6 is a receptor for AIEC in the intestinal mucosa, and increased CEACAM6 expression on the apical membrane of ileum cells promoted the abnormal colonization of AIEC in the ileum mucosa[ 9 ]. Furthermore, AIEC LF82 type I pili binding to CEACAM6 and TLR5 induced hiF-1A production and activated the classic NF-κB pathway, resulting in clinical colitis symptoms[ 10 ]. To mimic the high level of CEACAM6 expression in CD, transgenic CEABAC10-expressing mice were used to establish models expressing human CEACAMs.…”
Section: Introductionmentioning
confidence: 99%
“…FMT is a process in which feces from healthy people are transferred to patients, and it was first used to treat patients with recurrent Clostridium difficile infection. Recent studies have shown that FMT can significantly improve the composition of BAs in the gut of patients with C. difficile , increase the content of secondary BAs and prevent C. difficile colonization[ 141 ]. Because of its apparent efficacy in treating recurrent C. difficile infection, it has been applied to other intestinal diseases, such as IBD, IBS, and pancreatitis.…”
Section: Intestinal Flora Ba Metabolism and Ibdmentioning
confidence: 99%
“…In IBD studies, FMT has shown significant efficacy in inducing remission of UC. A study of UC in children showed that the gut microbiota and metabolome of FMT responders were significantly more similar to those of healthy people[ 141 ].…”
Section: Intestinal Flora Ba Metabolism and Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…These perturbations to fecal microbiome composition can directly impact host health. Recent research shows that Fecal Microbiota Transplants (FMT), which involve the transfer of fecal microbes from a healthy donor into the gastrointestinal tract of a recipient animal, show promise in treating or preventing a range of health conditions and improving health outcomes [17][18][19]. FMTs can repopulate the microbiome and restore fecal microbiome composition, diversity, and homeostasis by increasing microbiome diversity, enhancing the numbers of beneficial microbes, or outcompeting pathogens [17][18][19].…”
Section: Introductionmentioning
confidence: 99%